2013
DOI: 10.1093/eurpub/ckt085
|View full text |Cite
|
Sign up to set email alerts
|

Trends of overweight and obesity, physical activity and sedentary behaviour in Czech schoolchildren: HBSC study

Abstract: Background: The decline of physical activity (PA) and the increased prevalence of overweight and obese children have been discussed worldwide. This study assessed the trends in the prevalence of overweight and obesity, PA and sedentary behaviour in Czech school-aged children. Methods: A cross-sectional questionnaire from the Czech Republic was administered in cycles in 2002, 2006 and 2010 under the Health Behaviour in School-Aged Children (HBSC) study. In the study, 14 219 children aged 11–15 years participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
84
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 32 publications
11
84
1
7
Order By: Relevance
“…The remaining 9 studies for screen time, 13 studies for TV viewing, and 1 study for total sedentary behaviour reported null findings. Within 19 studies, significant associations with body composition were not observed across all sex groups (Dupuy et al 2011;Hardy et al 2012;Ismailov and Leatherdale 2010;Jones et al 2010;Mejia et al 2013;Nigg et al 2011;Rey-Lopez et al 2012;Sigmundova et al 2014;Suglia et al 2013;Vaezghasemi et al 2012), ethnic groups (Saab et al 2011), age groups (de Jong et al 2013;Seo and Niu 2014;Zhang et al 2012), geographical locations (Taber et al 2012;Tambalis et al 2013), days of the week (Liou et al 2010), or measures of body composition (Kuriyan et al 2012;Sluyter et al 2013). Inconsistent findings were observed for doing homework and reading and primarily null findings were observed for accelerometer-derived sedentary time, breaks, and bouts as well as computer use, and video game use with body composition.…”
Section: Body Compositionmentioning
confidence: 98%
“…The remaining 9 studies for screen time, 13 studies for TV viewing, and 1 study for total sedentary behaviour reported null findings. Within 19 studies, significant associations with body composition were not observed across all sex groups (Dupuy et al 2011;Hardy et al 2012;Ismailov and Leatherdale 2010;Jones et al 2010;Mejia et al 2013;Nigg et al 2011;Rey-Lopez et al 2012;Sigmundova et al 2014;Suglia et al 2013;Vaezghasemi et al 2012), ethnic groups (Saab et al 2011), age groups (de Jong et al 2013;Seo and Niu 2014;Zhang et al 2012), geographical locations (Taber et al 2012;Tambalis et al 2013), days of the week (Liou et al 2010), or measures of body composition (Kuriyan et al 2012;Sluyter et al 2013). Inconsistent findings were observed for doing homework and reading and primarily null findings were observed for accelerometer-derived sedentary time, breaks, and bouts as well as computer use, and video game use with body composition.…”
Section: Body Compositionmentioning
confidence: 98%
“…Differences in excessive screen time were observed among girls and boys. While boys use computer more frequently than girls, in case of excessive watching TV, they do not differ, as the TV viewing is the most popular screen activity in leisure time among youth at all (21). Generally, more common activities among boys in comparison with girls are the internet or noninternet computer gaming and other similar computer use (19) which could impact higher amounts of overall screen time among boys (18).…”
Section: S34mentioning
confidence: 99%
“…The interest in sedentary behaviour, physical activity as well as health is still growing (17)(18)(19)(20), but there are only few studies reporting findings from Central European countries (21,22). However, in these countries, including Slovakia, are observed negative trends of lifestyle among adolescents in terms of increasing sedentary behaviour at the expense of physical activity and health complaints in comparison with other countries in Europe (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the presented data, we monitored physical activity recommendations fulfilment per week in accordance with the following criteria: performing vigorous physical activity minimally 3 times per week for 20 minutes (V 3 × 20), performing medium physical activity minimally 5 times per week for 30 minutes (M 5 × 30), continual walking minimally 5 times per week for 30 minutes (W 5 × 30), and daily physical activity for 60 minutes (Sum 7 × 60) [26].…”
Section: Methodsmentioning
confidence: 99%